TYPOLOGICAL ANALYSIS IN TEACHING A FOREIGN LANGUAGE - Abdullayeva Umida Nigmatullayevna; Jurakulova Raykhon Kholboyevna (Journals Park Publishing, 2022)
Typological classification is the process of describing the various linguistic types found across languages for some grammatical parameter, such as grammatical number or the formation of relative clauses.
Keywords: typology; analysis; comparison